Process Mining and User Privacy in D2D and IoT Networks - Muhammad Usman (14150391) (2019)
As the communication industry is moving towards the 5th generation (5G) of cellular networks and beyond, the traffic it carries is also becoming a mixture of higher and lower data rate rate traffic originating from cellular users and Internet-of-Things (IoT) networks, respectively. The main industries where IoT has found its applications include, but are not limited to, automotive, manufacturing, supply chain, agriculture, healthcare, and energy. All the aforementioned industries have their specific quality of service (QoS) requirements in terms of bandwidth, latency, and storage regarding the transmission of the data they generate. For instance, vehicle-to-everything (V2X) communication in the automotive industry requires ultra-low latency without any need for higher bandwidth; however, the IoT networks employed in agriculture generally require lower latency and lower bandwidth communication. Other Information Published in: Informatik Spektrum License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00287-019-01212-y